TARANTULAS (Araneae: Theraphosidae) FROM THE MIDDLE PUTUMAYO BASIN, LORETO, PERU - PANDURO VASQUEZ, Richard Augusto (2024)
Theraphosidae represent the family with the greatest diversity in the Mygalomorphae suborder, but the scarcity of studies in the Peruvian Amazon has generate uncertainty about its richness, reason that encourages to determine the species of tarantulas located the middle basin of the Putumayo river (Peru). Sampling was carried out in two communities: Puerto Arturo and Bobona, riparian populations, along pre-established transects and occasional manual collecting outside the transects; allspecimens were identified using taxonomic keys, descriptions and information available on web pages. Ten individuals were recorded, distributed in seven species, three belonging to the subfamily Theraphosinae, two to Avicularinae, one to Ischnocolinae and one to Psalmonpoeinae. This work aims to presents preliminary results of the diversity of tarantulas in the Putumayo river basin in indicating. The presence of least seven species in four subfamilies.